Optimasi Support Vector Machine Berbasis Particle Swarm Optimization Untuk Mendeteksi Hate Speech Pilkada Karawang - Wahyuningrum Ayu; Rijal Abdulhakim; Yuyun Umaidah; Jajam Haerul Jaman (Politeknik Negeri Batam, 2021)
The rise of hate speech on social media can harm various parties, including the candidate for regional head of Karawang Regency in 2020, but because of the large number of comments, the sanctions given to violators are not evenly distributed. To make it easier for Bawaslu to give sanctions to violators and to provide a deterrent effect to the Karawang community so that hate speech does not occur again. Therefore, this study was conducted by classifying positive and negative comments. The methodology used is Knowledge Discovery in Database (KDD) by dividing the data into 4 scenarios. The results obtained state that the Support Vector Machine (SVM) Algorithm with scenario